Strategi Pengembangan Kebijakan Pariwisata di Kabupaten Rejang Lebong Provinsi Bengkulu Tahun 2025 - Wijayanti, Zetia; Pratiwi, Novitry; Adzan, Galuh Efnol (Universitas Batanghari Jambi, 2025)
The purpose of this study is to analyze the tourism policy development strategy in Rejang Lebong Regency by identifying strengths, weaknesses, opportunities and threats, namely SWOT analysis so that it can produce a tourism policy development strategy using 4 components of tourism development, namely attraction, amenities, accessibility, and ancillary service. The method used is a literature review from various sources related to the tourism policy development strategy in previous studies, government reports and the mass media. The results of this study found that the tourism policy strategy in Rejang Lebong Regency is still not optimal. This is evidenced by the many tourist attractions that are not equipped with supporting facilities and infrastructure, such as toilets, parking lots, and other public facilities.